1988
DOI: 10.1287/mnsc.34.12.1450
|View full text |Cite
|
Sign up to set email alerts
|

Dynamically Updating Relevance Judgements in Probabilistic Information Systems Via Users' Feedback

Abstract: A decision maker's performance relies on the availability of relevant information. In many environments, the relation between the decision maker's informational needs and the information base is complex and uncertain. A fundamental concept of information systems, such as decision support and document retrieval, is the probability that the retrieved information is useful to the decision maker's query. This paper presents a sequential, Bayesian, probabilistic indexing model that explicitly combines expert opinio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1992
1992
2003
2003

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…In fact, in situations involving many uncertain variables, each of which must be combined in making the calculation, the certainty we place on a given predictive probability may be negligible. Tague (1973) and Lenk and Floyd (1988) described the uncertainty in predictive probabilities of relevance by using probability distributions. The intent of these systems is to adequately model the uncertainty inherent in IR systems and to compensate for inadequate system design by incorporating the inquirer's judgements through Bayes theorem.…”
Section: Uncertainty In the Probability Of Relevancementioning
confidence: 99%
See 2 more Smart Citations
“…In fact, in situations involving many uncertain variables, each of which must be combined in making the calculation, the certainty we place on a given predictive probability may be negligible. Tague (1973) and Lenk and Floyd (1988) described the uncertainty in predictive probabilities of relevance by using probability distributions. The intent of these systems is to adequately model the uncertainty inherent in IR systems and to compensate for inadequate system design by incorporating the inquirer's judgements through Bayes theorem.…”
Section: Uncertainty In the Probability Of Relevancementioning
confidence: 99%
“…Instead, the inquirer's query and the documents' descriptions are sufficient information for the system to produce predictive probabilities, and additional information, such as the inquirer's relevance judgements about other documents, is superfluous. Other authors, such as Bookstein (1983) and Lenk and Floyd (1988), have considered models with dependent assessments.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Not surprisingly, outside of the professional press, most of the ES research is reported in the management information system and computer science literatures. These studies focus on analyses of ES feasibility (Goul & Tong, 1987), case studies of applications (Sviokla, 1990), issues related to ease of use (Lamberti & Wallace, 1990), and evaluations of alternative methods of knowledge acquisition and representation (Hoffman, Shadbolt, Burton, & Klein, 1995;Lenk & Floyd, 1988;Liang, 1992;Tou, 1985;Wright & Ayton, 1987). Research into the effects of ESs on users reports that ESs generally improve individual performance and learning (Fedorowicz, Oz, & Berger, 1992;Lamberti & Wallace, 1990;Moffitt, 1994;Sviokla, 1990).…”
mentioning
confidence: 99%
“…To improve the system's capability of correctly estimating the user preferences, a learning component called the relevance feedback mechanism often is incorporated within the basic structure of an IRS. 11,27,28 This component concentrates on allowing a retroaction controlled by the user in order to improve the retrieval results on the basis of further indications, which allow the system to learn the real user preferences. Figure 3 shows the scheme of an IRS with a relevance feedback mechanism.…”
Section: Systems For Information Accessmentioning
confidence: 99%